KOMUNITAS ENCLAVE CURAHLEDUK DALAM SISTEM KEKERABATAN UNTUK EKONOMI BERKELANJUTAN - Arodha, Dianidza (Jurnal Dialektika Politik, 2025)
The diversity that Indonesian people have is spread across various regions which creates uniqueness because they have different cultural, linguistic, racial, and religious backgrounds and each ethnic group maintains and maintains cultural values so that they continue to apply, even though from time to time is experiencing developments in the globalization era with the entry of new values, so that cultural values experience shifts and changes in the framework of advancing community development, in this case, changes in attitudes and behavior patterns, as self-potential to sustain and improve the lives of local communities. The Curahleduk people have traditions that make them survive. Even though they are on the slopes of a mountain which can be said to be primitive or marginalized, they are still able to maintain what has become their traditions and customs in terms of social solidarity among the Curahhleduk people, when in fact modernity has become endemic in this area. This study aims to, 1) identify and describe the conception of the Curahleduk community regarding the kinship system, 2) explain the form of parental kinship practices in the Curahleduk community, and 3) describe the kinship system related to social solidarity.